Internet of Things and Blockchain Technologies in the Insurance Sector - Ahmad, Shakil; Saxena, Charu (2022 3rd International Conference on Computing, Analytics and Networks (ICAN), 2022)
With cutting-edge technologies like Blockchain technology, the Internet of Things (IoT), and Artificial Intelligence, the insurance industry is entering a new era of advancements. Financial innovations are widely affecting economic activities. IoT and blockchain technologies are considerably aiding the expansion of the insurance industry in this new era. This article examines the impact of IoT and blockchain technologies on the insurance industry and describes the phenomena from several angles. Digital insurers are growing more popular now, but it is essential to understand the problems and challenges they face, which result in poor penetration. Although there are many advantages for the insured and insurer, internet insurance providers are subject to operational, regulatory, and company reputation. Customers worry about the safety of their transactions and identity theft. This article aims to illustrate the fundamentals and the significance of IoT and blockchain technologies in the insurance business, looking at the benefits that accrue to the insurance provider and the customer. The findings of the study observed that Blockchain technology helps reduce insurers' administrative costs of insurers and ensure the insured person's claim adjustment. On the other hand, the Internet of Things helps to share more information about the clients and mitigate risk.